Impact of MDRs on COVID-19 Patients Among Developing Countries - Bharadwaj, Alok (Coronaviruses, 2025)
The COVID-19 virus has killed more than 6.3 million people worldwide. The misuse of antibiotics increased during epidemics, leading to the spread of MDRs. Although antibiotic use is increasing in both developed and developing countries, the utility level and abuse are higher in developing countries. This could have negative consequences for the vaccine, especially considering that many developing countries reported the emergence of many resistant microbes even before the pandemic. Infectious diseases, social and cultural pressures, and telemedicine facilities can all contribute to the overuse of antibiotics. The emergence of multidrug resistance is a major concern, especially in developing countries where health services are already inadequate and diagnostic capacity and facilities for disease prevention and control are inadequate. This might be the major cause of the extensive spread of such diseases. Improper waste management and disposal in hospitals and communities make it easy for clean water to leak from the area, causing many diseases and causing many antibiotics. The potential for microplastics to be turned into anti-bacterial products is also of particular concern for low- and middle-income countries. In the present review, we aim to examine the impact of multidrug resistance in ESKAPE infections coupled with healthcare-associated infections and determine their risk of secondary infection in COVID-19 patients in low- and middle-income countries during the COVID-19 epidemic from a multidisciplinary perspective, identify the challenge for developing countries and seek solutions to solve this problem.
Keywords: global pandemic